Transcription Factors Controlling Primary and Secondary Metabolism in Filamentous Fungi: The β-Lactam Paradigm - García-Estrada, Carlos; Domínguez-Santos, Rebeca; Kosalková, Katarina; Martín, Juan-Francisco (Fermentation (Basel), 2018)
Transcription factors are key regulatory proteins in all living beings. In fungi, transcription factors include either broad-domain regulatory proteins that affect the expression of many genes involved in biosynthetic processes, or proteins encoded by cluster-associated (also called pathway-specific) regulatory genes. Belonging to the most interesting transcription factors in fungi are binuclear zinc finger proteins. In addition to the transcription factors in the strict sense, other proteins play a very important role in the expression of genes for primary and secondary metabolism in fungi, such as winged helix regulators, the LaeA protein and the velvet complex. LaeA appears to be involved in heterochromatin reorganization, and the velvet complex proteins, which are nuclear factors that associate with LaeA, also have a determining role in both differentiation (sporulation) and secondary metabolite biosynthesis. The genes involved in the biosynthesis of β-lactam antibiotics are well known and serve as an excellent model to understand the transcriptional control of genes involved in the biosynthesis of secondary metabolites. Interaction between different regulatory proteins in the promoter regions may represent a cross-talk regulation between different gene clusters.